Prognostic value of added stratification of circumferential resection margin status in oesophageal carcinoma. Issue 5 (26th March 2013) - Ahmad, Jawad; Loughrey, Maurice B; Donnelly, David; Ranaghan, Lisa; Shah, Rajeev; Napolitano, Giulio; Kennedy, Andrew J
<x xml:space="preserve">Abstract</x> Aims Involved circumferential resection margin (CRM) (R1) in oesophageal carcinoma (OC) has conflicting definitions. This study aimed to compare two such definitions applied to a cohort of OC resection specimens and also evaluated a novel three‐tier CRM stratification. Methods and results OC patients with pT3 disease were classified as R0 or R1 on the basis of Royal College of Pathologists (UK) (RCPath) and College of American Pathologists (CAP) criteria and group survivals were compared. Patients were then stratified into three groups on the basis of tumour distance from the CRM (>1 mm, 0.1–1 mm, 0 mm). A total of 195 patients were included. According to RCPath criteria, 50 resections were R0 and 145 R1; median survival was 72.0 and 18.1 months. Using CAP criteria, 137 resections were R0 and 58 R1; median survival was 30.1 and 12.6 months. Using three‐tier stratification, tumour was clear by >1 mm (R0) in 50 cases, 0.1–1 mm from CRM (RCPath R1; CAP R0) in 87 cases and 0 mm (R1) in 58 cases; median survival was 72.0, 24.6 and 12.6 months, respectively. Survival difference was statistically significant using each binary system and also the three‐tier system. Conclusions Both RCPath and CAP criteria to define CRM have similar prognostic value. A novel three‐tier classification of CRM status provides more detailed prognostication.